Characterization of uropathogenic ESBL-producing Escherichia coli isolated from hospitalized patients in western Algeria - Zenati, Fatima; Barguigua, Abouddihaj; Nayme, Kaotar; Benbelaïd, Fethi; Khadir, Abdelmounaïm; Bellahsene, Chafika; Bendahou, Mourad; Hafida, Hassaïne; Timinouni, Mohammed (The Journal of Infection in Developing Countries, 2019)
Introduction: The aim of this study is to assess the prevalence and molecular characterization of uropathogenic Extended spectrum β-lactamases (ESBLs) producing Escherichia coli. Methodology: During 3 years, all hospitalized patients at the University-affiliated hospital of Tlemcen and presenting urinary tract infections caused by E. coli were considered as potential study participants. These E. coli isolates were examined phenotypically for ESBL production. ESBL strains were subjected to antimicrobial susceptibility testing and were investigated for the presence of plasmid mediated quinolone resistance genes, 16SrRNA methylase genes and virulence genes by using conventional PCR and DNA sequencing. The molecular characterization of ESBL strains was established by phylogenetic grouping method and ERIC-PCR. Results: The overall prevalence of ESBL was 32.5%. The blaCTX-M-15 was the most frequently detected in ESBL isolates, followed by blaCTX-M-14, blaCTX-M-28, blaCTX-M-1 and blaSHV-12 respectively. The plasmid-mediated quinolone resistance genes were detected in the 15 ESBL strains with the aac(6’)-Ib-cr gene was the most detected followed by qnrB1 and qnrA1 gene respectively. Among the 22 ESBL isolates resistant to gentamicin and amikacin, the 16SrRNA methylase genes were detected in 4 isolates. The sfa and pap virulent genes were founds in 26% and 22% of isolates receptively. The genotyping analysis of all strains revealed that almost were belonged to phylogenetic groups A1 and A0 and fourteen distinct clones. Conclusion: The emergence of uropathogenic ESBL isolates and the high rate of blaCTX-M are alarming in Algeria. Strict measure must be required to control the further spread of these strains in Algerian hospitals.